2011
DOI: 10.1074/jbc.m111.270926
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-microRNA-222 (Anti-miR-222) and -181B Suppress Growth of Tamoxifen-resistant Xenografts in Mouse by Targeting TIMP3 Protein and Modulating Mitogenic Signal

Abstract: Background: MicroRNAs-221/222 and 181b are up-regulated in tamoxifen-resistant breast cancer. Results: Anti-miRs-222/181b regressed tamoxifen-resistant xenografts. Down-regulation of TIMP3, a common target of these miRs, facilitated growth factor signaling by regulating metalloproteases. Conclusion: Survival of tamoxifen-resistant breast cancer is dependent on miR-mediated suppression of TIMP3. Significance: Anti-miRs-222/221 and -181b can be used to render tamoxifen-resistant tumors responsive to the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 39 publications
4
65
0
Order By: Relevance
“…Accumulating evidence has demonstrated that microRNA-222 (miR-222) plays a crucial role in cell growth, oncogenesis, invasion, migration and drug resistance in tumor cells (17,18), and overexpression of miR-222 has been found in several types of cancers, such as breast cancer, colorectal carcinoma, glioblastoma, colorectal carcinoma, as well as liver cancer (19)(20)(21)(22)(23). In particular, several studies demonstrated that miR-222 is involved in resistance to several chemotherapeutic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that microRNA-222 (miR-222) plays a crucial role in cell growth, oncogenesis, invasion, migration and drug resistance in tumor cells (17,18), and overexpression of miR-222 has been found in several types of cancers, such as breast cancer, colorectal carcinoma, glioblastoma, colorectal carcinoma, as well as liver cancer (19)(20)(21)(22)(23). In particular, several studies demonstrated that miR-222 is involved in resistance to several chemotherapeutic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…As a member of the miR-181 family, miR-181b also may play a role in the variation in tumorigenesis among different cancers, and its decreased expression is inversely correlated with increased protein levels of the myeloid cell leukemia sequence 1-and B-cell lymphoma 2-targeted genes (Ji et al, 2009;Chen et al, 2010). miR-181b may also contribute to drug resistance of tamoxifen in breast cancer and tumor progression of gastric carcinomas (Jiang et al, 2011;Lu et al, 2011;Visone et al, 2012). In our study, the higher expression of miR-181b in signet-ring cell carcinoma compared with that in tubular adenocarcinoma suggests a correlation with the more malignant clinical behavior of signet-ring cell carcinoma.…”
Section: Discussionsupporting
confidence: 53%
“…Recently, it has been indicated that these miRNAs induce resistance to the selective ER downregulator, and this was caused by the activation of β-catenin and the repression of transforming growth factor-β-mediated growth inhibition. 54 Lu et al 55 demonstrated that miR-221, miR-222 and miR-181b directly target tissue inhibitor of metalloproteinases (TIMP)3, and MCF7 cells that had been subjected to TIMP3 knockdown were found to be able to Figure 2 Biogenesis and function of microRNA (miRNA). miRNA genes are transcribed by RNA polymerase II (Pol II) in the nucleus to generate primary miRNA (pri-miRNA).…”
Section: Mirna In Hormone Receptor-positive/her2-negative Breast Cancermentioning
confidence: 99%